Lithuania's Attempts of the 1920 Summer to Recover its Lands Occupied by the Poles - Vytautas Lesčius (Lietuvos Istorijos Studijos)
Complicated and hostile relations between Poland and Lithuania developed since the very beginning of the restored independence. The Polish ruling strata of society were unwilling to recognize independent Lithuania and resorted to diverse measures to subjugate her. Under the pretext of the fight against the Bolsheviks, the Poles occupied a vast territory of Lithuania by the beginning of the 1920 summer. A state of undeclared war arose between Lithuania and Poland.